The mediating effect of leverage and dividend policy on the influence of corporate governance towards firm value - Soewarno, Noorlailie; Yulia Arifin, Stephanie; Tjahjadi, Bambang (2017)
This study examines the mediating effect of leverage and dividend policy on the influence of corporate governance towards firm value.This is a quantitative study used secondary data of 181 companies listed on the Indonesian Stock Exchange (IDX) in the year of 2014.The results showed that leverage did not mediate corporate governance-firm value relationship, and devidend policy partially mediated corporate governance-firm value relationship